STRATEGI MENGHADAPI COBAAN DALAM AL-QUR’AN (Pemaknaan Tekstual dan Kontekstual terhadap Qs. Al-Baqarah : 155) - Afandi, Irfan; Mahmud, M. Amir (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2020)
Humans will definitely get a trial or disaster. The study of the trials of Allah SWT in the Qur'an is more about the justification of good and bad, there are still rarely studies that mention how the strategy of being a